2013
DOI: 10.2460/ajvr.74.5.712
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of three formulations of hydroxyethyl starch solutions on coagulation and platelet function in horses

Abstract: Dilution of blood samples with all HES solutions resulted in changes in viscoelastic coagulation and platelet function that did not appear to be attributable to dilution alone. In vivo evaluations are necessary to understand the clinical impact of these in vitro changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…The decrease in vWF and fVIII activities as a result of HES administration is a phenomenon that has been reported in many human25 and some veterinary3, 14 studies, and likely contributes to the impaired ability of the platelets to aggregate, especially under conditions of high shear. The most frequently cited hypothesis for the drop in these factors is that the HES molecules bind to the vWF/fVIII complex and speed excretion from circulation.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The decrease in vWF and fVIII activities as a result of HES administration is a phenomenon that has been reported in many human25 and some veterinary3, 14 studies, and likely contributes to the impaired ability of the platelets to aggregate, especially under conditions of high shear. The most frequently cited hypothesis for the drop in these factors is that the HES molecules bind to the vWF/fVIII complex and speed excretion from circulation.…”
Section: Discussionmentioning
confidence: 81%
“…The instrument used for this study was chosen over thromboelastography because more significant changes were found during previous in vitro testing in horses 14. Coagulation effects were not as prominent using viscoelastic testing as previous in vitro work in horses14 and humans 18, 27.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations